The experiences of East Asian dementia caregivers in filial culture: a systematic review and meta-analysis - Wang, Qian; Xiao, Xiaohua; Zhang, Jin; Jiang, Dongdong; Wilson, Amanda; Qian, Beiran; Song, Peige; Yang, Qian (Frontiers in Psychiatry, 2023)
Background With the aging population in East Asia, the prevalence of dementia and the need for patient care is increasing. Family caregivers of people with dementia are at risk of physical and mental health problems. Filial piety culture regulates relationships within East Asian families and effects the well-being and behavior of dementia family caregivers (CGs). Objective To systematically assess the experience of East Asian dementia caregivers in filial culture. Methods: Electronic databases, including MEDLINE, APA PsycINFO, CINAHL (via EBSCOhost), Web of Science, and Cochrane Library, were searched for relevant studies up to July 2021. Only original articles were included. Results Thirteen eligible studies were included, of which eight were qualitative and five were quantitative. Meta-analysis showed a negative association (r = −0.18, 95%CI [−0.28, −0.08]) between filial culture and caregiver burden. The quantitative studies identified four themes related to dementia caregivers’ experiences: (1) Recognition and understanding of filial piety as part of cultural identity, (2) Role transitions- from child to CG, (3) Filial piety’s constraints on CGs; (4) CGs’ self-compassion through changing cultural norms of filial practice. Conclusion Filial culture influences the whole process behind caregiving for East Asian dementia caregivers. At the same time, cultural transition has also brought about new connotations and practices to filial culture.